Identification and Characterization of Adipose Tissue-Derived Human Antibodies With “Anti-self” Specificity - Frasca, Daniela; Diaz, Alain; Romero, Maria; Garcia, Denisse; Jayram, Diya; Thaller, Seth; del Carmen Piqueras, Maria; Bhattacharya, Sanjoy; Blomberg, Bonnie B. (Frontiers in Immunology, 2020)
We have previously shown that the human obese adipose tissue (AT) contributes to increased secretion of adipocyte-specific IgG antibodies in individuals with obesity. This occurs without any exogenous stimulation, because the ongoing process of cell death in the obese AT leads to the release of “self” antigens able to induce chronic stimulation of B cells. We have identified several mechanisms responsible for the release of “self” antigens, such as hypoxia, cell cytotoxicity and DNA damage. In this paper, we confirm and extend our initial observation on a different cohort of individuals, and we show that also the plasma of these individuals is enriched in IgG antibodies with specificities for adipocyte-derived antigens. Adipocyte-specific IgG secreted in the obese AT are significantly correlated with those present in plasma. Using immunoprecipitation and mass spectrometry, we have identified these antigenic specificities. The antigens are almost exclusively intracellular or cell-associated antigens, usually not recognized as “self” antigens, but they are released by cells dying in the AT. We also show for the first time that the adipocytes in the obese AT stimulate the secretion of IgG autoimmune antibodies, and they do so because they express the antigen-presenting molecules CD1d and, to a much lesser extent, MHC class II. These results may lead to the development of novel therapeutic strategies to control autoimmunity.